Specific features of proliferation and apoptosis in non-invasive adenocarcinoma of endometrium and adenocarcinoma with invasion into myometrium - V. O. Tumanskiy; M. M. Baudarbekova; O. V. Chepets (Patologìâ)
Introduction. The development of tumors occurs as a multistage process, where each step corresponds to certain genetic changes of cells and it is a reflection characteristic of different histological forms of cancer. This usually multiple changes include the expression of several oncogenes and inactivation of two or more suppressor genes. Such events are a critical step in the transformation of normal cells into malignant. It is known that the pathogenesis of cancer of the endometrium is the imbalance result of the proliferative and apoptotic processes. Therefore it is particularly important to gain in-depth pathomorphological study of uterine mucosa from cellular and molecular determination of prognosis of tumors that includes immunohistochemical (IHC) diagnostic markers of proliferative activity and apoptosis processes. These studies are aimed to differential diagnosis of invasive and non-invasive adenocarcinomas of the endometrium (AE).